Histologic Characterization of Polymethylmethacrylate Dermal Filler Biostimulatory Properties in Human Skin. Issue 12 (December 2019) - Ronan, Stephen J.; Eaton, Laura; Lehman, Alayne; Pilcher, Brian; Erickson, Christof P.
Abstract : BACKGROUND: Little literature exits on the mechanism of action of implanted polymethylmethacrylate (PMMA) filler. OBJECTIVE: To characterize PMMA-induced dermal extracellular matrix production in the skin. MATERIALS AND METHODS: Single-center, open-label prospective study in healthy volunteers undergoing removal of redundant skin was injected intradermally and subdermally with PMMA dermal filler (Bellafill). Punch biopsies were harvested over a time course and evaluated for the deposition of collagen-3 and procollagen-1, proteoglycans and elastin using immunohistochemistry. Blinded histopathologic readings were performed by a dermatopathologist to characterize the nature of the dermal extracellular matrix findings. RESULTS: Normal inflammatory infiltrate was exhibited at all timepoints after PMMA injection with an influx of fibroblasts and new vasculature. Tissue proteoglycans were noted within the injectate beginning at Week 1 and persisted through the study end point. Increased collagen Type 3 was evident following the first week after injection, peaked at Month 2 and diminished through Months 3 through 6. Procollagen-1 was noted at Month 1 and continued to increase in intensity and organization through the study end point (6 months). Elastin staining was inconclusive. Polymethylmethacrylate microspheres remained within the initial injection area and became encapsulated within new collagen fibers. The growth and pattern of new connective tissue mimicked a normal wound healing response. CONCLUSION: Polymethylmethacrylate-collagen gel filler stimulates collagen-3 and procollagen-1 when injected into human skin. This combination of neocollagenesis followed by microencapsulation of PMMA microspheres in the new tissue provides for long-lasting results.